Reciprocating internal combustion engines : performance Part 1. Standard refrence conditions and declarations of power (BSI, 1977)
Reciprocating engines, Internal combustion engines, Prime movers, Performance, Power (mechanics), Fuel consumption, Lubricating oils, Declarations, Rated power, Pressure measurement (fluids), Formulae (mathematics)